Sustainable Farming: Respons Petani Tanaman Pangan terhadap Kepemilikan Lahan Pertanian - Pratiwi, Anik; Moeis, Jossy Prananta (Jurnal Ekonomi dan Pembangunan Indonesia, 2022)
Sustainable agricultural practices are the best solution to resolve widespread degradation of agricultural land in Indonesia. However, application of this practices in Indonesia are still very limited. Many empirical studies show that private agricultural land is an incentive that encourages farmers to apply sustainable agricultural practices. This research aimed to analyze relationship between agricultural land ownership and adoption of sustainable agriculture practices. The main data source used is 2017 Food Crop Cost Structure Survey. OLS and 2SLS methods are applied to estimate impact of agricultural land ownership. Regression results indicate that private land motivates farmers to adopt sustainable agricultural practices.